2012
DOI: 10.1007/s12282-012-0397-3
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of primary small cell carcinoma of the breast showing non-mass-like pattern on diagnostic imaging and histopathology

Abstract: Primary small cell carcinoma of the breast is a rare breast cancer. We report two cases of this entity showing a non-mass-like pattern on multimodality images and histopathology. Both women presented with a breast mass, and one had axillary lymphadenopathy. Both cases revealed fine calcification on mammography (MMG) and an irregularly shaped, hypoechoic lesion on ultrasonography. Computed tomography (CT) and magnetic resonance imaging (MRI) showed non-mass-like enhancement in both cases. Dynamic MRI showed med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…In our study, many other malignant lesions, such as IDC, lymphatic metastatic poorly differentiated adenocarcinoma, adenocarcinoma and acute lymphatic leukaemia also appeared as non-mass lesions. Studies have demonstrated that infiltrating lobular carcinoma (ILC), primary small cell carcinoma and breast lymphoma could show a non-masslike pattern on US as well [11,12]. Not only malignant lesions, but also non-malignant lesions can also appear as non-mass-like lesions, such as adenosis, intraductal papilloma and plasma cell mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, many other malignant lesions, such as IDC, lymphatic metastatic poorly differentiated adenocarcinoma, adenocarcinoma and acute lymphatic leukaemia also appeared as non-mass lesions. Studies have demonstrated that infiltrating lobular carcinoma (ILC), primary small cell carcinoma and breast lymphoma could show a non-masslike pattern on US as well [11,12]. Not only malignant lesions, but also non-malignant lesions can also appear as non-mass-like lesions, such as adenosis, intraductal papilloma and plasma cell mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…SWE is the US-based imaging modality, which can depict histologic information by evaluating the mechanical index of tissue (elasticity) (8), so as to differentiate between benign and malignant lesions. SWE has shown potential for differentiating benign from malignant breast disease and could possibly reduce the breast biopsy rate (9)(10)(11)(12)(13). Study of Zhou et al (13) showed that "the stiff rim sign" offered important diagnostic performance for breast lesions, and combination of conventional US and stiff rim sign had the potential to improve the differentiation of breast lesions.…”
Section: Introductionmentioning
confidence: 99%
“…When DCIS is larger and SCC is fewer in proportion components of PSCCB, the imaging findings were analogous to that of DCIS. [3] When SCC accounts for the majority and DCIS is less, the tumor shows a high degree of malignancy and rapid growth, which often leads to the formation or necrosis of central “scar-like fibers.” Therefore, the multimodality imaging depicted the breast lesion as a mass with a clear margins, a high intra-tumoral signal intensity on T2-weighted images, low ADC value, heterogeneous rim enhancement, and plateau or wash-out pattern, [4] these imaging findings were analogous to that of the triple negative breast cancer (TNBC). In our case, the multimodal imaging findings were similar to that of TNBC, suggesting that the pathologic components of PSCCB are predominated by SCC and DCIS ranks the secondary position, which are consistent with the pathologic report of this case.…”
mentioning
confidence: 99%